New approaches to language attitudes in the Hispanic and Lusophone world - Bugel, Talia; Montes-Alcalá, Cecilia (Issues in Hispanic and Lusophone linguistics, 2020)
"The analysis of language attitudes is important not only because attitudes can affect language maintenance and language change but also because such reflections and discussions can bring light to social, cultural, political and educational matters that require an interdisciplinary approach. This volume fills a crucial void in the field of Hispanic and Lusophone linguistics by introducing the latest production in the discipline of attitudes toward Spanish, Spanish sign language, Portuguese, Guarani and Papiamentu around the world, from South America and the Caribbean to the United States, Spain and Japan. The studies presented in this collection--a variety of sociolinguistic scenarios and methodological approaches--will make an important contribution to theoretical discussions on linguistic attitudes, specifically in the domains of language integration through education, language policy, and language maintenance. This book is intended for sociolinguists, social scientists and scholars in the humanities as well as graduate students enrolled in sociolinguistics courses"--